Inclusion of Students with Disability in Physical Education: Analysis of Trends and Best Practices (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
Inclusive physical education for students with disability evolved in line with ethical requirements and stakeholder morality. While inclusive physical education is embraced at a conceptual level and desired at the classroom level, the complexity of successful implementation often remains overlooked in policy and curriculum guidelines. The writing in this study uses a literature study by utilizing the scientific journal's index in Scopus from 1992 to 2022 by involving a total of 298 documents. The theme of last years was about developing media with a subject focus on prospective teachers and students of physical education as research subjects. Currently, the research theme of students with disability in physical education is studying with a focus on developing awareness toward disabilities in physical education. In future research, physical educators conceptually embraced inclusive physical education with a creative outlook for collaboration, knowledge, and support. Cooperative and supportive efforts between physical educators, students with disability, parents, and teacher aides are valued in creating physical education environments that effectively respond to learner diversity. While access to practical teaching guidance remains scarce, this study may contribute to physical educator practice.